Simon Kuznets and Russia: An uneasy relation - Moshé Syrquin (Duke University, Center for the History of Political Economy (CHOPE), 2021)
Simon Kuznets was born and educated in Russia and the Soviet Ukraine. He completed his economic education and adopted his research methodology in the United States where Wesley Mitchell was a major influence during his early career. Though scarred by the trauma of displacement, eviction, and discrimination before emigration he regarded the early Soviet regime with an unbiased and mildly sympathetic scholar's eye. This changed drastically by 1930, apparently as a result of the Stalinist dictatorial regime and the hounding of kindred spirit economists. He fell silent on all things Russian for three decades. The debates on Soviet industrialization in the early 1920s influenced his major study on the economic growth of nations, and when the study was well underway he reengaged with Soviet economics with a devastating appraisal of its performance. Some of his work was influenced by his heritage, particularly his Jewish roots. Overall, his relation with Russia and the Soviet Union was truly an uneasy one.
Keywords: B1; B2; B31; E01; O57; 330; Simon Kuznets; Modern Economic Growth; Soviet industrialization; Jewish heritage